2007
DOI: 10.1071/py07020
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy in Primary Health Care

Abstract: Health literacy is fundamental if people are to successfully manage their own health. This requires a range of skills and knowledge about health and health care, including finding, understanding, interpreting and communicating health information, seeking of appropriate care and making critical health decisions. A primary health system that is appropriate and universally accessible requires an active agenda based on research of approaches to address low health literacy, while health care providers should be ale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 21 publications
3
60
0
Order By: Relevance
“…Low levels of health literacy have been found to negatively affect health outcomes and is considered to be a more accurate predictor of health status than determinants of health such as, socioeconomic status, education, employment, race or gender [34]. Low literacy skills also predict the degree with which individuals engage in the health system and their understanding of their chronic illness [35]. There is an urgent need for health literacy to be integrated at the system level to improve patients’ quality of care and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of health literacy have been found to negatively affect health outcomes and is considered to be a more accurate predictor of health status than determinants of health such as, socioeconomic status, education, employment, race or gender [34]. Low literacy skills also predict the degree with which individuals engage in the health system and their understanding of their chronic illness [35]. There is an urgent need for health literacy to be integrated at the system level to improve patients’ quality of care and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this context the newly learned skills enabled the participants to overcome contextual issues that were potentially influencing their thinking and behaviour and that were forestalling their intentions to become proactive and self-determined in their well-being (48) . Research in the Aboriginal context relating to the development of health literacy suggests that individuals who experience increased self-efficacy and competence, autonomy (identified relevance to personal needs) and feel relatedness (behaviours modelled, valued or prompted by significant others) are more likely to be selfdetermined in relation to their health (48)(49)(50) . The present study also identified potential barriers to successful development of community empowerment and governance through the ongoing effects of local family tensions and community mistrust of outside individuals, groups and/or organisations (37,(51)(52)(53)(54) .…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is defined as the capacity to obtain, process, and use basic health information and services needed to make health decisions. 33 44 Another issue that is applicable to veterans is mental health literacy, which incorporates the ability to recog nize specific disorders; knowledge of causes, risk factors, self-treatments, and available professional help; as well as attitudes that promote recognition and appropriate help seeking.45 Related to health literacy and health commu nication, studies of subpopulations of veterans have found that female veterans often have problems managing numeri cal information regarding the benefits of mammograms46; whereas, outpatient veterans showed lower numeracy scores than those at a University-based clinic.47 Further, inadequate health literacy in primary care veterans was a predictor of worse satisfaction with health care after adjusting for patient sociodemographics. 48 One study examined the distribution of health literacy numeracy and graph literacy for African-American and older veterans.…”
Section: Introductionmentioning
confidence: 99%